Involvement of Parkin‐mediated mitophagy in the pathogenesis of chronic obstructive pulmonary disease‐related sarcopenia. Issue 3 (3rd April 2022) - Ito, Akihiko; Hashimoto, Mitsuo; Tanihata, Jun; Matsubayashi, Sachi; Sasaki, Ryoko; Fujimoto, Shota; Kawamoto, Hironori; Hosaka, Yusuke; Ichikawa, Akihiro; Kadota, Tsukasa; Fujita, Yu; Takekoshi, Daisuke; et al.
Abstract: Background: Sarcopenia is characterized by the loss of skeletal muscle mass and strength and is associated with poor prognosis in patients with chronic obstructive pulmonary disease (COPD). Cigarette smoke (CS) exposure, a major cause for COPD, induces mitochondrial damage, which has been implicated in sarcopenia pathogenesis. The current study sought to examine the involvement of insufficient Parkin‐mediated mitophagy, a mitochondrion‐selective autophagy, in the mechanisms by which dysfunctional mitochondria accumulate with excessive reactive oxygen species (ROS) production in the development of COPD‐related sarcopenia. Methods: The involvement of Parkin‐mediated mitophagy was examined using in vitro models of myotube formation, in vivo CS‐exposure model using Parkin −/− mice, and human muscle samples from patients with COPD‐related sarcopenia. Results: Cigarette smoke extract (CSE) induced myotube atrophy with concomitant 30% reduction in Parkin expression levels ( P  < 0.05). Parkin‐mediated mitophagy regulated myotube atrophy by modulating mitochondrial damage and mitochondrial ROS production. Increased mitochondrial ROS was responsible for myotube atrophy by activating Muscle Ring Finger 1 (MuRF‐1)‐mediated myosin heavy chain (MHC) degradation. Parkin −/− mice with prolonged CS exposure showed enhanced limb muscle atrophy with a 31.7% reduction in limb muscle weights ( P  < 0.01) and 2.3 times greater MuRF‐1 expression ( P  < 0.01) compared with wild‐type mice with concomitant accumulation of damaged mitochondria and oxidative modifications in 4HNE expression. Patients with COPD‐related sarcopenia exhibited significantly reduced Parkin but increased MuRF‐1 protein levels (35% lower and 2.5 times greater protein levels compared with control patients, P  < 0.01 and P  < 0.05, respectively) and damaged mitochondria accumulation demonstrated in muscles. Electric pulse stimulation‐induced muscle contraction prevented CSE‐induced MHC reduction by maintaining Parkin levels in myotubes. Conclusions: Taken together, COPD‐related sarcopenia can be attributed to insufficient Parkin‐mediated mitophagy and increased mitochondrial ROS causing enhanced muscle atrophy through MuRF‐1 activation, which may be at least partly preventable through optimal physical exercise.